Caffeine Supplementation or Carbohydrate Mouth Rinse Improves Performance - Pereira, Paulo Eduardo Assis; Azevedo, Paulo; Azevedo, Katia; Azevedo, Warleyson; Machado, Marco (International Journal of Sports Medicine, 2020)
Training volume is one of the critical variables required to promote resistance training benefits (e. g., hypertrophy, muscular strength). Thus, strategies to improve training volume are required. We tested the hypothesis that there is an increase in performance and reduction in the rate of perceived exertion in strength training with caffeine supplementation, carbohydrate mouth rinse, and a synergistic effect of caffeine supplementation plus carbohydrate mouth rinse. We recruited 29 physically active women: 24±4 years, 60.0±7.9 kg, 161.0±6.0 cm. This study was a double-blind, randomized, placebo-controlled, and crossover one. The subjects performed all sessions of strength training under different conditions: caffeine (6.5 mg·kg−1 body mass); carbohydrate (6 g of maltodextrin rinsed for 10 s); caffeine plus carbohydrate; or placebo. We applied the ANOVA for repeated measures through the null-hypothesis statistical test, and the Bayes factors analyses approach. The subjects showed significant improvement in the total repetitions (P<0.01; BF10 ~99%) for both lower and upper limb exercises in all conditions compared to placebo without difference among interventions. The rate of perceived exertion (P>0.05) did not differ among interventions. However, BF10 analyses showed a higher probability of lower RPE for CAF intervention. We conclude that either caffeine supplementation or carbohydrate mouth rinse can improve performance in resistance training. There is no additional effect of caffeine plus carbohydrate.
Keywords: exercise; resistance exercise; fatigue; perceived exertion